Theme Markedness in EFL Students’ Recount Texts: A Systemic Functional Analysis - Hanafiah, Ridwan; Yusuf, Muhammad; Aswani, Aprilza (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2018)
This study is aimed to discover the types and the dominant type of theme markedness in EFL students’ recount texts based on the theory of systemic functional linguistics. Qualitative content analysis approach was utilized in this study. Writing sheets were utilized as the instruments of collecting the data. The data were in the form of clauses taken from 33 recount texts written by second-year students of English literature department of University of Sumatera Utara. Based on the analysis, it was discovered that there were 1144 clauses in the data. Then, in terms of theme markedness, marked theme (MT) had 213 occurrences (18.62%) and unmarked theme (UMT) had 931 occurrences (81.38%). The conclusion can be drawn that there were 2 types of markedness namely marked theme (MT) and unmarked theme (UMT), and the dominant type of theme markedness was unmarked theme (UMT). It means that the students dominantly used unmarked theme in their recount texts.Keywords: markedness, theme, recount text, systemic functional, content analysis